Analgesic Efficacy of Intraoperative Superior Hypogastric Plexus (SHP) Block during Abdominal Hysterectomy: A Systematic Review and Meta-Analysis of Controlled Trials - Hany Salem; Ibtihal Abdulaziz Bukhari; Maha Al Baalharith; Nasser AlTahtam; Safa Alabdrabalamir; Mohammed Ziad Jamjoom; Saeed Baradwan; Ehab Badghish; Mohammed Abuzaid; Fatimah Shakir AbuAlsaud; Osama Alomar; Abdullah Alyousef; et al. (Medicina, 2023)
Background and Objectives: Abdominal hysterectomy is a major surgery that is often associated with pronounced postsurgical pain. The objective of this research is to conduct a systematic review and meta-analysis of all randomized controlled trials (RCTs) and nonrandomized comparative trials (NCTs) that have surveyed the analgesic benefits and morbidity of intraoperative superior hypogastric plexus (SHP) block (intervention) compared with no SHP block (control) during abdominal hysterectomy. Materials and Methods: The Cochrane Central Register of Controlled Trials (CENTRAL), Google Scholar, Web of Science, PubMed, Scopus, and Embase were searched from inception until 8 May 2022. The Cochrane Collaboration tool and Newcastle–Ottawa Scale were used to evaluate the risk of bias of RCTs and NCTs, respectively. In a random effects mode, the data were pooled as risk ratio (RR) or mean difference (MD) with 95% confidence interval (CI). Results: Five studies (four RCTs and one NCT) comprising 210 patients (SHP block = 107 and control = 103) were analyzed. The overall postsurgical pain score (n = 5 studies, MD = −1.08, 95% CI [−1.41, −0.75], p < 0.001), postsurgical opioid consumption (n = 4 studies, MD = −18.90 morphine milligram equivalent, 95% CI, [−22.19, −15.61], p < 0.001), and mean time to mobilization (n = 2 studies, MD = −1.33 h, 95% CI [−1.98, −0.68], p < 0.001) were significantly decreased in the SHP block group contrasted with the control arm. Nevertheless, there was no significant variance between both arms regarding operation time, intraoperative blood loss, postsurgical NSAID consumption, and hospital stay. There were no major side effects or sympathetic block-related aftermaths in both groups. Conclusions: During abdominal hysterectomy and receiving perioperative multimodal analgesia, the administration of intraoperative SHP block is largely safe and exhibits better analgesic effects compared to cases without administration of SHP block.